Le cycle de la violence physique : trajectoire sociale et cheminement personnel de la violence individuelle et de groupe - LeBlanc, Marc (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1990)
This article is about interpersonal physical violence. The description of the course of violent crimes in Quebec, based on official statistics and surveys, shows an increase in these crimes and in gang fighting, but the level is equivalent to that we had already known. There are a number of factors responsible for this situation — recent immigration, the reappearance of adolescent gangs and certain social changes. An analysis of interpersonal violence by means of a longitudinal study of individuals shows that it is an activity of the youth, not often repeated and of short duration, which is preceded by other criminal activities. It has been established that there is a strong continuity between agressive acts in early childhood, fighting during adolescence and violent crimes during adulthood. It has also been shown that the appearance of this type of conduct can be predicted under certain conditions. The results call for several preventive measures: the integration of young immigrants, the development of mechanisms for adolescent conviviality, support during the transition from school to the workplace and energetic control of adolescent gangs. Concerning action with regard to individuals, we discuss early discovery of persons at risk and specific types of intervention.